A HuR/TGF-β1 feedback circuit regulates airway remodeling in airway smooth muscle cells. Issue 1 (December 2016) - Wang, Na; Yan, Di; Liu, Yi; Liu, Yao; Gu, Xianmin; Sun, Jian; Long, Fei; Jiang, Shujuan
Abstract Background Asthma is a worldwide health burden with an alarming prevalence. For years, asthma-associated airway injury remains elusive. Transforming growth factor β1 (TGF-β1) is a pleiotropic cytokine that has been shown to be involved in the synthesis of the matrix molecules associated with airway remodeling. Human antigen R (HuR), the member of the Hu RNA-binding protein family, can bind to a subset of short-lived mRNAs in their 3′ untranslated regions (UTR). However, the functional roles and relevant signaling pathways of HuR in airway remodeling have not been well illustrated. Thus, we aim to explore the relationship between HuR and TGF-β1 in platelet derived growth factor(PDGF)-induced airway smooth muscle (ASM) cells and asthmatic animal. Methods Cultured human ASM cells were stimulated by PDGF for 0, 6, 12 and 24 h. Western blotting, RT-PCR and immunofluoresence were used to detect the expression of HuR, TGF-β1, α-smooth muscle actins (α-SMA) and collagen type I (Col-I). Then knockdown of HuR, flow cytomerty was used to detect the morphological change and western blotting for functionally change of ASM cells. Furthermore, the interference of TGF-β1 and exogenous TGF-β1 were implemented to testify the influence on HuR. A murine OVA-driven allergic model based on sensitization and challenge was developed. The inflammatory response was measured by bronchoalveolar lavage fluid (BALF), airway damage was analyzed by hematoxylin and eosin staining, airway remodeling was assessed by sirius red staining and periodic acid-schiff staining, the expression level of HuR, TGF-β1 and α-SMA were measured by RT-PCR, western blotting and immunohistochemistry. Results Here, we found that PDGF elevated HuR expression both at mRNA and protein level in cultured ASM cells at a time-dependent manner, which was simultaneously accompanied by the enhanced expression of TGF-β1, α-SMA and Col-I. Further study revealed that the knockdown of HuR significantly increased the apoptosis of ASM cells and dampened TGF-β1, Col-I and α-SMA expression. However, interfering TGF-β1 with siRNA or extra addition of TGF-β1, HuR could restore its production as well as Col-I. Compared with normal mice stimulating with PBS, OVA-induced mice owned high amount of inflammatory cells, such as eosinophils, lymphocytes and neutrophils except macrophages. HE staining showed accumulation of inflammatory cells surrounding bronchiole and sirius red staining distinguished collagen type I and III deposition around the bronchiole. Higher abundance of HuR, TGF-β1 and α-SMA were verified in OVA-induced mice than PBS-induced mice by RT-PCR, western blotting and immunohistochemistry. Conclusions A HuR/TGF-β1 feedback circuit was established to regulate airway remodeling in vivo and in vitro and targeting this feedback has considerable potential for the intervention of asthma.